2004
DOI: 10.1084/jem.20040495
|View full text |Cite
|
Sign up to set email alerts
|

The Loss of PTEN Allows TCR αβ Lineage Thymocytes to Bypass IL-7 and Pre-TCR–mediated Signaling

Abstract: The phosphatase and tensin homologue deleted on chromosome 10 (PTEN) negatively regulates cell survival and proliferation mediated by phosphoinositol 3 kinases. We have explored the role of the phosphoinositol(3,4,5)P3-phosphatase PTEN in T cell development by analyzing mice with a T cell–specific deletion of PTEN. Pten flox/flox Lck-Cre mice developed thymic lymphomas, but before the onset of tumors, they showed normal thymic cellularity. To reveal a regulatory role of PTEN in proliferation of developing T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
116
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(119 citation statements)
references
References 52 publications
3
116
0
Order By: Relevance
“…Previous studies have shown that an activated PKB Tg could enhance T cell survival in vivo [31,32], although these Tg mice developed autoimmunity and lymphoma, suggesting PKB-mediated transformation. Moreover, conditional deletion of phosphatase and tension homologue deleted on chromosome 10 that counteracts PKB, can bypass the dependence on IL-7 and pre-TCR signals in developing thymocytes [33], although again these mice developed T cell lymphomas. In both these cases, the PKB expression in the peripheral compartment was not restricted to naive T cells.…”
Section: Enforced Bcl-2 Expression Restores Peripheral C C -Naive Cd4mentioning
confidence: 99%
“…Previous studies have shown that an activated PKB Tg could enhance T cell survival in vivo [31,32], although these Tg mice developed autoimmunity and lymphoma, suggesting PKB-mediated transformation. Moreover, conditional deletion of phosphatase and tension homologue deleted on chromosome 10 that counteracts PKB, can bypass the dependence on IL-7 and pre-TCR signals in developing thymocytes [33], although again these mice developed T cell lymphomas. In both these cases, the PKB expression in the peripheral compartment was not restricted to naive T cells.…”
Section: Enforced Bcl-2 Expression Restores Peripheral C C -Naive Cd4mentioning
confidence: 99%
“…Pten fl/fl (Marino et al, 2002), PDK1 fl/fl (Mora et al, 2003), Lck-cre (Takahama et al, 1998), Rag2 / (Shinkai et al, 1992), and transgenic CD2-C3 (Cleverley et al, 1999) mice were bred and maintained in the Wellcome Trust Biocentre/ Transgenics Resource Unit, University of Dundee in compliance with UK Home Office Animals (Scientific Procedures) Act 1986 guidelines. Pten fl/fl Lck-cre +/ and PDK1 fl/fl Lck-cre +/ mice were generated as described previously (Hagenbeek et al, 2004;Hinton et al, 2004). Pten fl/fl Lck-cre +/ were generated by crossing mice with floxed PTEN alleles, floxed PDK1 alleles, and mice expressing Cre recombinase under the control of the proximal p56 lck promoter (Lck-cre +/ ).…”
Section: Methodsmentioning
confidence: 99%
“…PTEN haploinsufficient mice accordingly develop a wide range of tumors, including a high frequency of T lymphomas . Moreover, tissue-specific deletion of PTEN in hematopoietic stem cells or thymocytes using Cre-loxP strategies results in T leukemogenesis or lymphomagenesis (Suzuki et al, 2001;Hagenbeek et al, 2004;Ma et al, 2005;Yilmaz et al, 2006;Hagenbeek and Spits, 2008).…”
mentioning
confidence: 99%
“…Phosphatase and tensin homologue deleted on chromosome 10 (PTEN) is the major negative regulator of the PI3K/Akt signaling pathway, and its loss results in constitutive Akt activity (29). To test the concept that PI3K/Akt/mTOR signaling controls Foxp3, we compared the inducibility of Foxp3 in TCR/CD28 activated PTEN-deficient and control T cells (29) in response to the classical Foxp3 inducer TGF␤ versus PI3K inhibitors. The frequency of TGF␤-induced Foxp3 cells was considerably lower in PTEN-deficient than in control CD4 cells, but the PI3K inhibitor LY294002 restored Foxp3 induction in PTEN-deficient CD4 T cells (Fig.…”
Section: Premature Withdrawal Of Tcr Signals and Inhibitors Of The Pimentioning
confidence: 99%